RAYAP KAYU (ISOPTERA) PADA RUMAH-RUMAH ADAT MINANGKABAU DI SUMATERA BARAT - Ningsih, Deffi Surya; Julia, Za’aziza Ridha; Hilmi, Larissa; Darmi, Leo (Program Kreativitas Mahasiswa - Penelitian, 2013)
Minangkabau traditional houses in West Sumatra has a high historical value, but it has the serious damage caused by termite infestation. The purpose of this research was to determine the types of termites that attack Minangkabau traditional houses in West Sumatra, Research the wood termites (Isoptera) in Minangkabau traditional houses in West Sumatra have been conducted in March and July 2013. Direct sampling methods used for collecting termites on mikrosite. Three species of termites were found that belong to two subfamilies, those are Macrotermes gilvus Hagen, Macrotermes sp. (Macrotermitinae) and Nasutitermes matangensis Haviland (Nasutitermitinae). Keywords: Isoptera, Termitidae, Minangkabau traditional houses, Macrotermitinae, Nasutitermitinae.